DAMPAK BULLYING TERHADAP PERCAYA DIRI PESERTA DIDIK SEKOLAH DASAR - Chan, Faizal; Kurniawan, Agung Rimba; Kalila, Siti; Amalia, Fiki; Apriliani, Devi; Herdana, Sonya Verta (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
AbstractÂ The purpose of this study is to describe the impact of bulliying on the confidence of elementary school students